REDESIGN DAN PEMETAAN JARINGAN WLAN BERDASARKAN CAKUPAN AREA DI KANTOR DINAS PENDIDIKAN KAYUAGUNG - Irwansyah Irwansyah; Helda Yudiastuti (Jurnal Ilmiah Matrik, 2019)
Abstract : Wi-Fi technologies are widely used generally using IEEE 802 wireless standardization. 11a/b/g which works at a frequency of 2.4 GHz. These devices are found in almost all places, such as in offices – Government offices, private companies, entertainment venues, and educational venues. Currently the need for Wi-Fi (wireless fidelity) is very much needed, because nowadays many gadget devices that have been equipped with Wi-Fi so that with Wi-Fi Everyone can access the Internet everywhere. Based on the results of a field survey conducted on the WLAN network in the office of the Dinas Pendidikan Kayuagung in South Sumatera, from all computer units in the office is connected to the Internet through a network cable or wireless network, that the wireless network felt is still less optimal because there are some areas that are not covered or affordable by the Wi-Fi network. The researcher aims to redesign and rebrand Wi-Fi networks based on the scope of the area to be more optimal. While the research method to be used is the method PPDIOO (Prepare Plan Design Implement Operate and Optimize).